Organizational mentoring, what about protégé needs? - Knackstedt, Janine Elke Ursula (University of Waterloo, 2001)
Whereas studies in organizations have almost exclusively measured mentoring occurrences, this research on health care professionals has uniquely contributed to the mentoring literature in two ways. First, the importance of examining mentoring needs from the protege's perspective has been empirically demonstrated. Six types of mentoring needs were identified, namely professional development, sponsorship and recognition, equal partnership, friendship, coaching on work issues, and role-modeling. From a theoretical perspective, the six mentoring needs disconfirm Kram's (1983, 1985a) two-dimensional model of mentoring. Furthermore, the construct of mentoring needs was different from the construct of mentoring occurrences. In other words, what proteges need in terms of mentoring behaviour is different from what they are receiving. From a practical perspective, determining mentoring needs is important because: (1) employees have different needs; (2) mentors provide different mentoring functions according to their own skills, abilities, personal style, and motivation; (3) it allows for a better match between individual and organizational needs; (4) it is a proven benefit during times of organizational change and restructuring; (5) it can be used as a powerful tool for leaders who wish to assess the climate of their organization; and (6) it may significantly increase the effectiveness of formalized mentoring programs. Second, this research has demonstrated the value in examining the gender composition of the dyad in future mentoring research. Female proteges who had a male mentor distinguished themselves from their peers in that they expressed stronger mentoring needs than male proteges with male mentors, particularly for professional development, equal partnership, coaching on work issues, and role-modeling. They also reported receiving more mentoring functions compared to proteges in other dyads, specifically sponsorship and recognition, coaching on work issues, and role-modeling. A follow-up study revealed that female proteges who had a male mentor were not more competitive, more ambitious, nor more in need for power and achievement than their peers in other dyads. This is in keeping with other literature which suggests that sex differences on achievement-related motives and behaviours are small to non existent. Furthermore, these women were not more prone to seek help. With regards to the person consulted for specific mentoring behaviours, it was found that women approached women to discuss personal issues but they had no gender preference with regards to the person consulted for career developmental matters. Men, on the other hand, always approached men, regardless of the issue. Women who preferred consulting men for career advancement issues were younger, more junior, had a greater need for achievement, and tended to have a greater need for power than women who consulted women. In sum, this thesis has uniquely contributed to the mentoring literature by operationalizing the construct of mentoring needs and demonstrating the value of assessing mentoring needs in a organizational context. Furthermore, the importance of examining the gender composition of the mentoring dyad in future research has been demonstrated. Theoretical and practical implications are presented.
Keywords: Harvested from Collections Canada